2022
DOI: 10.1039/d2ta00491g
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of triazine-based graphitic carbon nitrideviaplasma-induced polymerisation of melamine

Abstract: Millisecond plasma pulses are used to convert vaporised melamine into pure TGCN with a large surface area for efficient water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…The optimized lattice parameter of the planar structure of tg-C 3 N 4 was obtained a = b = 4.78 Å, and its band structure exhibits a direct band gap (Γ → Γ) with an energy of 3.19 eV, which is consistent with theoretical work . However, using photoluminescence spectroscopy, it has been shown that the experimental bandgap of tg-C 3 N 4 (triazine type of g-C 3 N 4 ) is about 2.1 eV . This experimental band gap energy is closer to the PBE bandgap (∼1.6 eV) than to the HSE06 band gap.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The optimized lattice parameter of the planar structure of tg-C 3 N 4 was obtained a = b = 4.78 Å, and its band structure exhibits a direct band gap (Γ → Γ) with an energy of 3.19 eV, which is consistent with theoretical work . However, using photoluminescence spectroscopy, it has been shown that the experimental bandgap of tg-C 3 N 4 (triazine type of g-C 3 N 4 ) is about 2.1 eV . This experimental band gap energy is closer to the PBE bandgap (∼1.6 eV) than to the HSE06 band gap.…”
Section: Resultssupporting
confidence: 82%
“…49 However, using photoluminescence spectroscopy, it has been shown that the experimental bandgap of tg-C 3 N 4 (triazine type of g-C 3 N 4 ) is about 2.1 eV. 50 This experimental band gap energy is closer to the PBE bandgap (∼1.6 eV) than to the HSE06 band gap. The optimized lattice structure of the Janus WSSe monolayer unit cell and its corresponding electronic band structure are shown in Figure 1C,D, respectively.…”
Section: Janus Wsse and Triazine G-c 3 Nmentioning
confidence: 97%
“…This result could be attributed to the fact that the added SnCl 4 •5H 2 O accelerated the condensation reaction of melamine to generate involatile compounds, and thereby reduced the weight loss caused by the sublimation of melamine. 80,81 In summary, during the pyrolysis process of melamine, SnCl 4 •5H 2 O was converted into SnO 2 and HCl, which affected the morphology and structure of g-C 3 N 4 and increased the yield of g-C 3 N 4 , reflecting the advantages of the one-pot pyrolysis preparation strategy.…”
Section: Resultsmentioning
confidence: 99%
“…3c) exhibit four types of N species, including C-N]C (398.6 eV), N-(C) 3 (399.9 eV), NH x (401.1 eV), and the positive charge localization in heptazine ring amino groups (404.4 eV). 34 For TCN-Lc10, the binding energy of C 1s for N-C]N and C-NH x has a negative shi compared to that of BCN, which is due to the formation of chemical bonds between the Lc unit and C-NH x on BCN. Analogously, N 1s spectra for C-N]C and NH x are both shied to lower binding energy.…”
Section: Morphology and Structural Characterizationmentioning
confidence: 97%